Implementation of Teamwork in Students Using the Improvement Model Cycle at the Ibnu Sina Nursing Academy, Sabang City - Gressia, Rosa Galica Gita; Khairunisa, Aida; Aldani, Noor Asnidar; Al Kautsarina, Vara; Herdianto, Pulung (JURNAL KEBIDANAN, KEPERAWATAN DAN KESEHATAN (BIKES), 2025)
Nurses experience unexpected events due to a lack of non-technical skills, such as teamwork, which plays a crucial role in improving patient safety. This study aims to enhance the skills of nursing students in Sabang City in implementing teamwork through simulation methods. A quasi-experimental method with a pretest-posttest design without a control group was used to evaluate the effectiveness of teamwork implementation among 20 nursing students through the "PDSA Cycle" improvement model. The analysis results showed a significant increase in students' skills after implementing this method. The average self-assessment score before the intervention was 65.3 ± 7.8. As a follow-up, additional training for lecturers and clinical instructors in implementing team-based learning strategies is recommended to enhance students' skills during clinical practice in hospitals, thereby improving the quality of nursing education and ensuring patient safety in healthcare services.